Differentiation of Test Items between The High School Biology Olimpiad in North Kayong and The National Science Olimpiad (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
The purpose of this research is to find out the differentiation between high school biology olympiad in the District of North Kayong and the National Biology Olympiad. The analysis is used to provide feedback to students regarding their knowledge in the forms of factual, conceptual, procedural, and metacognitive traits. This research is a descriptive study consisting of two phases: the stage of designing test items carried out by four Biology teachers who joined the group, Science Teachers Council, and the test tryout phase given to 33 high school students of class XI. This research resulted in the dimensions of knowledge which indicates that there are 79% (63 items) being in the dimension of the factual, as much as 15% (12 items) in the conceptual, as much as 6% (5 items) in the procedural, while the metacognitive dimension is 0%. The question package which was given in the preliminary phase test was 5% considered difficult, while in the final stage such difficulty was not found (0%). Therefore, it is concluded that the question items need to be revised because they have differentiation between high school biology olympiad in the District of North Kayong and the National Biology Olympiad.